CALCULATION OF DYNAMICS OF TEMPERATURE CHANGING AT FILLING IN OF METALLIC MOLD - A. N. Chichko; L. V. Markov (Литьë и металлургия)
The results of calculations of dynamics of the temperature field changing of the metallic mode used at production of casting ''rack'* are presented. The method of analysis of volumetric temperature field of metallic mode in time, which allows to analyze the dynamics of the chill heating under influence of casting melt by frequency curves of a number of grid elements, is offered.